Resolving International Sports Disputes: An Exploration of Mediation and Conciliation - Ngatchou Toto Carles (Recent Trends in Sports, 2024)
The globalization of sports has led to an increase in cross-border disputes, necessitating effective and efficient dispute resolution mechanisms. Traditional litigation and arbitration methods often prove time-consuming, costly, and ineffective in preserving relationships. This research explores the role of Alternative Dispute Resolution (ADR) methods, specifically mediation and conciliation, in resolving international sports disputes. Through a comparative analysis of international sports organizations and dispute resolution mechanisms, this study examines the benefits and limitations of mediation and conciliation in international sports. The study examines how successfully alternative dispute resolution (ADR) preserves relationships, reputations, and expertise while also upholding mutual respect and trust between the parties. The results highlight how mediation and conciliation may be used to settle international sports conflicts quickly, confidently, and flexibly while taking into account the particular sensitivities of sporting environments. In order to improve its implementation, this study also emphasizes the need for institutional support and knowledgeable facilitators with training in sports-related ADR. The suggestions are meant to assist athletes, teams, leagues, governing bodies, and sports organizations in successfully putting ADR procedures into practice. This will help to create standardized best practices that are cognizant of the ever-changing global sports environment.
Keywords: Alternative Dispute Resolution; conciliation; dispute resolution; international sports; mediation; sports law